Perbandingan Metode Ekstraksi Maserasi, Sokletasi, Dan Sonikasi Terhadap Nilai Rendemen Ekstrak Rimpang Kunyit (Curcuma Longa L.) - Annisa Rahma Aryanti; Made Helen Susanti; Anjar Hermadi Saputro; Herayati; Indah Puspita Sari; Syahjoko Saputra, Iwan (PT. Pubsains Nur Cendekia, 2025)
This study aims to determine the comparison of maceration, soxhletation, and sonication extraction methods on the yield value of turmeric rhizome (Curcuma longa L.). Extraction was carried out using methanol and n-hexane solvents. The extraction process produces turmeric extract with different colors, textures, and aromas depending on the method used. The maceration, soxhletation, and sonication methods have different impacts on the yield of the extract, but the basic principle is the same in filtering active substances from the sample. The yield value obtained from the maceration method is 0.4996% soxhletation 0.0013% and sonication 0.0071%. The maceration method is proven to provide the highest extract yield compared to the soxhletation and sonication methods, which is 0.4996%.